2014
DOI: 10.1038/srep03798
|View full text |Cite
|
Sign up to set email alerts
|

Pre-seizure state identified by diffuse optical tomography

Abstract: In epilepsy it has been challenging to detect early changes in brain activity that occurs prior to seizure onset and to map their origin and evolution for possible intervention. Here we demonstrate using a rat model of generalized epilepsy that diffuse optical tomography (DOT) provides a unique functional neuroimaging modality for noninvasively and continuously tracking such brain activities with high spatiotemporal resolution. We detected early hemodynamic responses with heterogeneous patterns, along with int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 64 publications
5
26
0
Order By: Relevance
“…A method for fast DOT image reconstruction during rapidly changing neural dynamics was also achieved. Results suggest that early hemodynamic changes could be observed tens of seconds prior to seizure onset in awake rats, and confirms previous results in anesthetized animals 15 . Finally, a GPU-based image reconstruction algorithm was developed and tested with significant acceleration that allows real-time online monitoring of the pre-seizure state.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A method for fast DOT image reconstruction during rapidly changing neural dynamics was also achieved. Results suggest that early hemodynamic changes could be observed tens of seconds prior to seizure onset in awake rats, and confirms previous results in anesthetized animals 15 . Finally, a GPU-based image reconstruction algorithm was developed and tested with significant acceleration that allows real-time online monitoring of the pre-seizure state.…”
Section: Discussionsupporting
confidence: 91%
“…In the multi-GPU application with four GPU cards installed on the same computer, we generated four instances from the GPU-based code and ran them simultaneously. According to our previous phantom and rat experiments 15,22 , the 3D DOT reconstruction typically required 6 iterations to converge into a solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also reported similar positive correlation between hemodynamic signal and EEG PSD within gamma range. 35,38 DISCUSSION AND CONCLUSION We have conducted experiments based on the developed wPAT system using hyperoxia and acute PTZ-evoked seizure rat models. Results show that wPAT successfully detected cerebral HbO, HbR, and HbT changes of a rat when under hyperoxia by using 1,064, 710, and 797 nm wavelengths, respectively.…”
Section: Wearable Photoacoustic Tomography For Cerebral Blood Volume mentioning
confidence: 99%
“…Optical imaging techniques such as intrinsic optical signal (IOS) [4][5][6][7], diffuse optical tomography (DOT) [8][9][10], and spatial frequency domain imaging (SFDI) [11] overcome these limitations by achieving high-resolution, minimally invasive, imaging of the occurrence and propagation of neuronal and epileptic activity through changes in intrinsic tissue optical properties.…”
Section: Introductionmentioning
confidence: 99%